Penguatan Sumber Daya Manusia Pertahanan dalam Menghadapi Radikalisme, Konservatisme, dan Liberalisme Agama terhadap Ideologi Pancasila di Indonesia - Rahmat Effendi; Makmur Rizka (JURNAL PENDIDIKAN DAN PELATIHAN PERTAHANAN, 2025)
Non-military threats to Indonesia’s national defense are increasingly complex, as the growth of radicalism, conservatism, and religious liberalism has the potential to weaken social cohesion and erode Pancasila as the state ideology. These three spectrums of ideological threats operate through religious narratives, digital spaces, social networks, and political dynamics, thus demanding a defense response that is not only coercive but also ideological and cultural. This study aims to analyze the characteristics of religious-based ideological threats to Pancasila and formulate strategies for strengthening defense human resources (HR) in maintaining national ideological resilience. This study uses a qualitative approach, drawing on national defense regulations, counter-radicalization policies, official government documents, and academic literature, including books and articles from relevant national and international scholarly journals. The results show that religious radicalism encourages exclusivism and the legitimacy of violence, and religious conservatism breeds rigidity and resistance to national values. In contrast, religious liberalism has the potential to relativize collective values ​​and weaken ideological consensus. In this context, defense human resources play a strategic role as an ideological vanguard through a combination of hard and soft power approaches, including ideological education, digital literacy, counter-narratives, and collaboration with civil society. This research contributes theoretically by offering a conceptual model to strengthen defense human resources in upholding Pancasila, and practically by providing policy recommendations to enhance ideology-based non-military defense in Indonesia.